Membrane agent for wastewater treatment and preparation method thereof
By combining coal gangue and iron-based metal organic framework materials with modified polyacrylamide and carrying out coating treatment, the problems of poor adsorption method and secondary pollution in leather wastewater treatment were solved, and the effect of efficient pollutant removal was achieved.
Patent Information
- Application Number
- CN202510549940.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-06-13
AI Technical Summary
The prior art When treating leather wastewater, especially when the water quality is complex, the treatment effect of the adsorption method is not obvious and secondary pollution is easily generated.
Coal gangue and iron-based metal organic framework materials are used as raw materials, and radical polymerization is carried out through acid soaking, calcining and ultrasonic dispersion. The organic modified sodium-based bentonite, functional monomer and polyacrylamide are combined to form a modified polyacrylamide-coupled coal gangue/iron-based metal organic framework material composite, and the coating is carried out through fluidized bed technology to improve the treatment effect.
This method not only improves the adsorption and removal of pollutants in leather wastewater, but also enhances the cation binding capacity, significantly improves the treatment effect, and avoids secondary pollution.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water treatment, and more specifically, relates to a membranous agent for wastewater treatment and a preparation method thereof. Background Art
[0002] The leather industry is one of the important traditional industries in China, and leather products are widely used in fields such as shoes, clothing, and furniture. However, a large amount of wastewater is generated during the leather production process, and there are various toxic and harmful substances in the wastewater. How to effectively treat and reduce the environmental pollution caused by leather wastewater has become a major problem to be solved in the field of environmental protection.
[0003] Physical and chemical treatment technologies are widely used in the treatment of leather wastewater, and are particularly suitable for the removal of refractory organic pollutants, heavy metals, and high-concentration pollutants, such as precipitation, filtration, and adsorption technologies. The precipitation method removes solid pollutants in water through sedimentation by adding a coagulant or flocculant. The filtration method uses filter materials with different pore sizes to intercept particulate matter or suspended solids in the wastewater, and is commonly used in the primary treatment stage of wastewater. The adsorption technology makes full use of adsorbents (such as activated carbon, zeolite, etc.) to remove organic matter, heavy metal ions, and other dissolved pollutants in the wastewater. However, in the case of relatively complex water quality, the treatment effect of the adsorption method is not obvious.
[0004] In the treatment of leather wastewater, chemical precipitation and coagulation methods play an active role. Among them, the chemical precipitation method is to add corresponding chemical drugs into the water, and these drugs interact with the dissolved components in the water to generate insoluble substances. In the sedimentation tank, these insoluble substances will gradually precipitate. The coagulation method is to add a coagulant, such as polyaluminum chloride and polyferric sulfate. These two coagulants can coagulate tiny particles in the water into large particles. The sedimentation speed of the suspended matter is naturally increased, so as to better separate these suspended matters from the water body. Applying these two treatment methods to the treatment of leather wastewater can produce effective wastewater treatment effects, but it is easy to cause secondary pollution.
[0005] Therefore, it is very necessary to provide an agent for leather wastewater treatment. Summary of the Invention
[0006] The object of the present invention is to provide a membranous agent for wastewater treatment and a preparation method thereof, so as to effectively treat wastewater, especially leather wastewater.
[0007] To this end, the present invention provides the following technical solutions.
[0008] One aspect of the present invention provides a preparation method of a membranous agent for wastewater treatment, and the method includes the following steps:
[0009] S1: Take out the coal gangue after acid soaking, wash it with deionized water, then calcine and grind it to obtain coal gangue powder;
[0010] S2: Mix the obtained coal gangue powder and iron-based metal-organic framework material in a mass ratio of 1:1 - 3, then ultrasonically disperse the mixture in a silane coupling agent hydrolysis solution with a volume concentration of 0.1 - 0.5%, and stir at room temperature for 30 - 50 min to obtain a coal gangue / iron-based metal-organic framework material dispersion;
[0011] S3: Mix organically modified sodium-based bentonite, functional monomer, polyacrylamide and water in a mass-volume ratio of 1 g:1 g:1 - 2 g:50 - 100 mL, stir vigorously, then add an initiator and carry out a water bath heating and stirring reaction. After the reaction, ultrasonicate and let it stand for aging, and dry the obtained product to obtain modified polyacrylamide;
[0012] S4: Add the obtained modified polyacrylamide to the coal gangue / iron-based metal-organic framework material dispersion, stir for 12 - 16 h, then filter, wash and dry the obtained solid product to obtain a modified polyacrylamide-coupled coal gangue / iron-based metal-organic framework material composite;
[0013] S5: Dissolve the coating material in an organic solvent to obtain a coating solution with a mass fraction of 20 - 40%, then use a fluidized bed to spray the coating solution onto the surface of the modified polyacrylamide-coupled coal gangue / iron-based metal-organic framework material composite for coating. The obtained coated modified polyacrylamide-coupled coal gangue / iron-based metal-organic framework material composite is ultrasonically treated and dried in sequence to obtain the final product.
[0014] Preferably, in step S1,
[0015] The acid soaking is: soak the coal gangue in acid and stir at 200 - 400 rpm at room temperature for 30 - 60 min;
[0016] The calcination is: calcine the washed coal gangue at 400 - 600 °C for 4 - 10 h.
[0017] Preferably, the acid is selected from at least one of hydrochloric acid, nitric acid and sulfuric acid.
[0018] Preferably, in step S2, the silane coupling agent hydrolysis solution is obtained by dissolving a silane coupling agent in ethanol, and the silane coupling agent is selected from any one of mercapto trimethoxysilane, mercapto triethoxysilane, mercapto methyl trimethoxysilane, mercapto methyl triethoxysilane, mercapto methyl tripropoxysilane.
[0019] Preferably, in step S3, the preparation method of the organically modified sodium-based bentonite includes the following steps:
[0020] (i) Add sodium-based bentonite to water in a mass-to-volume ratio of 1 g: 10 - 30 mL, heat and stir in a water bath at 50 - 70 °C for 1 - 3 h, then ultrasonicate for 20 - 40 min and let stand for 3 - 5 h to obtain a sodium-based bentonite slurry.
[0021] (ii) Add a surfactant to the obtained sodium-based bentonite slurry, heat and stir in a water bath at 60 - 80 °C for 1 - 3 h to obtain an organically modified sodium-based bentonite.
[0022] Preferably, in step (ii), the surfactant is a quaternary ammonium salt surfactant selected from any one of dodecyl trimethyl ammonium bromide, dodecyl trimethyl ammonium chloride, tetradecyl trimethyl ammonium bromide, tetradecyl trimethyl ammonium chloride, hexadecyl trimethyl ammonium bromide, and hexadecyl trimethyl ammonium chloride.
[0023] Preferably, in step (ii), the addition amount of the surfactant is 1 - 3% of the mass of the sodium-based bentonite.
[0024] Preferably, in step S3, the functional monomer is selected from one or more of maleic anhydride, maleic acid, styrenesulfonic acid, vinylbenzoic acid, and vinylphosphonic acid.
[0025] Preferably, in step S3, the initiator is selected from any one of potassium persulfate, ammonium persulfate, and sodium persulfate.
[0026] Preferably, in step S3, the addition amount of the initiator is 0.3 - 0.6% of the mass of the functional monomer.
[0027] Preferably, in step S4, the addition amount of the modified polyacrylamide is 1 - 3 times the mass of the coal gangue / iron-based metal-organic framework material.
[0028] Preferably, in step S5, the coating material is selected from one or more of polyolefin, polyurethane, natural rubber, urea-formaldehyde resin, and epoxy resin.
[0029] Preferably, in step S5, the organic solvent is selected from one or more of tetrachloroethylene, dichloromethane, n-hexane, xylene, and acetone.
[0030] By means of the above technical solution, the present invention has at least the following advantages:
[0031] The present invention uses coal gangue and iron-based metal-organic framework materials as one of the raw materials. After acid soaking and calcination, coal gangue can obtain a porous structure. The iron-based metal-organic framework material is a porous crystalline material formed by self-assembly of iron ions as metal nodes and organic ligands through coordination bonds. This material shows great application potential in the fields of catalysis, adsorption, etc. The two substances are mixed and then placed in a silane coupling agent hydrolysis solution for surface coupling modification to endow the material with functionality. On the other hand, organically modified sodium bentonite, functional monomers, and polyacrylamide are used as raw materials, and a free radical polymerization reaction is carried out under the action of an initiator to obtain modified polyacrylamide. This product contains a large number of negative charges and has a high cation binding ability. The obtained modified polyacrylamide is connected to the coal gangue / iron-based metal-organic framework material through the bridging action of a silane coupling agent to obtain a modified polyacrylamide-coupled coal gangue / iron-based metal-organic framework material composite. This composite not only has an adsorption function but also has a cation binding ability, and can effectively remove pollutants in leather wastewater. Finally, the obtained modified polyacrylamide-coupled coal gangue / iron-based metal-organic framework material composite is coated, which can increase the contact area between the product and sewage, ensure the stability of the treatment process, and improve the decontamination effect.
[0032] The above description is only an overview of the technical solution of the present invention. In order to be able to understand the technical means of the present invention more clearly and implement it according to the content of the specification, the following describes the preferred embodiments of the present invention in detail. Detailed implementation manners
[0033] In order to make the technical means, creative features, achieved purposes, and functions of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.
[0034] Unless otherwise specified, the iron-based metal-organic framework material involved in the following embodiments is prepared according to the following method: Mix a 0.3 mol / L terephthalic acid / DMF solution and a 0.5 mol / L Fe(NO 3 ) 3 ·9H 2 O / DMF solution, ultrasonically dissolve and mix evenly, then react at 120 °C for 12 h. After the reaction, centrifuge at 10000 rpm for 5 min, and wash the obtained precipitate with ethanol to obtain the iron-based metal-organic framework material (hereinafter referred to as Fe-MOF).
[0035] Unless otherwise specified, the organically modified sodium bentonite involved in the following examples was prepared according to the following method: Sodium bentonite was added to water in an amount of 1 g: 20 mL by mass-volume ratio and stirred in a water bath at 60 °C for 2 h, then sonicated for 30 min and left standing for 4 h to obtain a sodium bentonite slurry. Dodecyltrimethylammonium bromide (the addition amount was 2% of the mass of sodium bentonite) was added to the obtained sodium bentonite slurry and stirred and reacted in a water bath at 70 °C for 2 h to obtain organically modified sodium bentonite.
[0036] Example 1:
[0037] The coal gangue was soaked in a hydrochloric acid solution with a concentration of 10 wt% and stirred at 300 rpm at room temperature for 45 min, then taken out, washed with deionized water, calcined at 500 °C for 7 h, and finally ground and passed through an 80-mesh sieve to obtain coal gangue powder.
[0038] The obtained coal gangue powder and Fe-MOF were mixed evenly in a mass ratio of 1:2 and then ultrasonically dispersed in a hydrolysis solution of mercapto trimethoxysilane with a volume concentration of 0.3%, and stirred at room temperature for 30 - 50 min to obtain a coal gangue / Fe-MOF dispersion.
[0039] Organically modified sodium bentonite, styrene sulfonic acid, polyacrylamide and water were mixed evenly in an amount of 1 g: 1 g: 1.5 g: 75 mL by mass-volume ratio and then strongly stirred, and then ammonium persulfate (the addition amount was 0.45% of the mass of styrene sulfonic acid) was added for stirring and reacting in a water bath. After the reaction, it was sonicated and left standing for aging, and the obtained product was dried to obtain modified polyacrylamide.
[0040] The obtained modified polyacrylamide (the addition amount was 2 times the mass of coal gangue / Fe-MOF) was added to the coal gangue / Fe-MOF dispersion and stirred for 14 h, then filtered, and the obtained solid product was washed and dried to obtain a coal gangue / Fe-MOF composite coupled with modified polyacrylamide.
[0041] Polyethylene was dissolved in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 30%. Then, the air inside the fluidized bed equipment was heated to 75 °C by a heater, and then the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was added to the fluidized bed through a feeding device to make the particles in a stable fluidized state; when the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was heated to 50 °C, the polyethylene solution was pressurized, and the flow rate was controlled at 10 g / cm 2 , and the polyethylene solution was sprayed onto the particle surface. Through the continuous driving of the fluidized bed, all sides of the particles would be evenly sprayed with the solute material, and finally a complete coating would be formed. Water was added to the obtained coal gangue / Fe-MOF composite coupled with modified polyacrylamide after coating, and then it was sonicated and dried in sequence to obtain the final product.
[0042] Example 2
[0043] The coal gangue was soaked in a hydrochloric acid solution with a concentration of 10 wt%, stirred at 400 rpm at room temperature for 30 min, then taken out, washed with deionized water, calcined at 600 °C for 4 h, and finally ground and sieved through a 80-mesh sieve to obtain coal gangue powder.
[0044] The obtained coal gangue powder was mixed with Fe-MOF in a mass ratio of 1:3, and then ultrasonically dispersed in a hydrolyzate of mercapto triethoxysilane with a volume concentration of 0.1%, and stirred at room temperature for 50 min to obtain a coal gangue / Fe-MOF dispersion.
[0045] Organically modified sodium bentonite, vinyl benzoic acid, polyacrylamide and water were mixed in a mass-volume ratio of 1 g:1 g:2 g:100 mL, stirred strongly, and then ammonium persulfate (the addition amount was 0.3% of the mass of vinyl benzoic acid) was added for water bath heating and stirring reaction. After the reaction, it was ultrasonicated and left to age, and the obtained product was dried to obtain modified polyacrylamide.
[0046] The obtained modified polyacrylamide (the addition amount was 1 times the mass of coal gangue / Fe-MOF) was added to the coal gangue / Fe-MOF dispersion and stirred for 12 h, then filtered, and the obtained solid product was washed and dried to obtain a coal gangue / Fe-MOF composite coupled with modified polyacrylamide.
[0047] Polyethylene was dissolved in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 40%. Then, the air inside the fluidized bed equipment was heated to 75 °C by a heater, and then the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was added to the fluidized bed through a feeding device to make the particles in a stable fluidized state; when the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was heated to 50 °C, the polyethylene solution was pressurized, and the flow rate was controlled at 10 g / cm 2 , and the polyethylene solution was sprayed onto the particle surface. Through the continuous driving of the fluidized bed, each surface of the particles would be evenly sprayed with the solute material, and finally a complete coating would be formed. After adding water to the obtained coated coal gangue / Fe-MOF composite coupled with modified polyacrylamide, it was ultrasonicated and dried in sequence to obtain the final product.
[0048] Example 3
[0049] The coal gangue was soaked in a hydrochloric acid solution with a concentration of 10 wt%, stirred at 200 rpm at room temperature for 60 min, then taken out, washed with deionized water, calcined at 400 °C for 10 h, and finally ground and sieved through a 80-mesh sieve to obtain coal gangue powder.
[0050] The obtained coal gangue powder and Fe-MOF were mixed evenly in a mass ratio of 1:1, and then ultrasonically dispersed in a hydrolyzed solution of mercaptomethyltrimethoxysilane with a volume concentration of 0.1%. Stir at room temperature for 30 min to obtain a coal gangue / Fe-MOF dispersion.
[0051] Organically modified sodium bentonite, maleic anhydride, polyacrylamide and water were mixed evenly in a mass-volume ratio of 1 g:1 g:1 g:50 mL and then vigorously stirred. After that, ammonium persulfate (the addition amount was 0.6% of the mass of maleic anhydride) was added for water bath heating and stirring reaction. After the reaction, ultrasonic treatment and static aging were carried out, and the obtained product was dried to obtain modified polyacrylamide.
[0052] The obtained modified polyacrylamide (the addition amount was 3 times the mass of coal gangue / Fe-MOF) was added to the coal gangue / Fe-MOF dispersion and stirred for 16 h. Then, filtration was carried out, and the obtained solid product was washed and dried to obtain a coal gangue / Fe-MOF composite coupled with modified polyacrylamide.
[0053] Polyethylene was dissolved in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 20%. Then, the air inside the fluidized bed equipment was heated to 75 °C by a heater. Then, the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was added to the fluidized bed through a feeding device to make the particles in a stable fluidized state; when the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was heated to 50 °C, the polyethylene solution was pressurized, and the flow rate was controlled at 10 g / cm 2 and the polyethylene solution was sprayed onto the particle surface. Through the continuous driving of the fluidized bed, each surface of the particles would be evenly sprayed with the solute material, and finally a complete coating would be formed. Water was added to the obtained coal gangue / Fe-MOF composite coupled with modified polyacrylamide after coating, and then ultrasonic treatment and drying were carried out in sequence to obtain the final product.
[0054] Comparative Example 1:
[0055] The coal gangue was ground and passed through an 80-mesh sieve to obtain coal gangue powder. The obtained coal gangue powder and Fe-MOF were mixed evenly in a mass ratio of 1:2, and then ultrasonically dispersed in a hydrolyzed solution of mercaptotrimethoxysilane with a volume concentration of 0.3%. Stir at room temperature for 30 - 50 min to obtain a coal gangue / Fe-MOF dispersion.
[0056] Organically modified sodium bentonite, styrenesulfonic acid, polyacrylamide and water were mixed evenly in a mass-volume ratio of 1 g:1 g:1.5 g:75 mL and then vigorously stirred. After that, ammonium persulfate (the addition amount was 0.45% of the mass of styrenesulfonic acid) was added for water bath heating and stirring reaction. After the reaction, ultrasonic treatment and static aging were carried out, and the obtained product was dried to obtain modified polyacrylamide.
[0057] The obtained modified polyacrylamide (with an addition amount being 2 times the mass of coal gangue / Fe-MOF) was added to the coal gangue / Fe-MOF dispersion and stirred for 14 h, and then filtered. The obtained solid product was washed and dried to obtain a coal gangue / Fe-MOF composite coupled with modified polyacrylamide.
[0058] Polyethylene was dissolved in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 30%. Then, the air inside the fluidized bed equipment was heated to 75 °C by a heater. Subsequently, the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was added to the fluidized bed through a feeding device to make the particles in a stable fluidized state. When the coal gangue / Fe-MOF composite coupled with modified polyacrylamide was heated to 50 °C, the polyethylene solution was pressurized, and the flow rate was controlled at 10 g / cm 2 , and the polyethylene solution was sprayed onto the particle surface. Through the continuous driving of the fluidized bed, each surface of the particles would be evenly sprayed with the solute material, and finally a complete coating was formed. After adding water to the obtained coal gangue / Fe-MOF composite coupled with modified polyacrylamide after coating, it was subjected to ultrasonic treatment and drying in sequence to obtain the final product.
[0059] Comparative Example 2:
[0060] Fe-MOF was ultrasonically dispersed in a hydrolyzed solution of 0.3% mercapto trimethoxysilane by volume concentration and stirred at room temperature for 30 - 50 min to obtain a Fe-MOF dispersion.
[0061] Organically modified sodium-based bentonite, styrene sulfonic acid, polyacrylamide, and water were mixed evenly in an amount according to the mass-volume ratio of 1 g:1 g:1.5 g:75 mL and then strongly stirred. Subsequently, ammonium persulfate (with an addition amount being 0.45% of the mass of styrene sulfonic acid) was added for water bath heating and stirring reaction. After the reaction ended, it was subjected to ultrasonic treatment and static aging, and the obtained product was dried to obtain modified polyacrylamide.
[0062] The obtained modified polyacrylamide (with an addition amount being 2 times the mass of Fe-MOF) was added to the Fe-MOF dispersion and stirred for 14 h, and then filtered. The obtained solid product was washed and dried to obtain a Fe-MOF composite coupled with modified polyacrylamide.
[0063] Polyethylene was dissolved in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 30%. Then, the air inside the fluidized bed equipment was heated to 75 °C by a heater. Subsequently, the Fe-MOF composite coupled with modified polyacrylamide was added to the fluidized bed through a feeding device to make the particles in a stable fluidized state. When the Fe-MOF composite coupled with modified polyacrylamide was heated to 50 °C, the polyethylene solution was pressurized, and the flow rate was controlled at 10 g / cm 2, the polyethylene solution is sprayed onto the surface of the particles. Through the continuous driving of the fluidized bed, each surface of the particles will be evenly sprayed with the solute material, and finally a complete coating will be formed. After adding water to the obtained modified polyacrylamide-coupled Fe-MOF composite with a coating, it is successively subjected to ultrasonic treatment and drying to obtain the final product.
[0064] Comparative Example 3:
[0065] The coal gangue is soaked in a hydrochloric acid solution with a concentration of 10 wt% and stirred at 300 rpm at room temperature for 45 min, then taken out, washed with deionized water, calcined at 500 °C for 7 h, and finally ground and sieved through a 80-mesh sieve to obtain coal gangue powder.
[0066] The obtained coal gangue powder is ultrasonically dispersed in a hydrolyzed solution of mercapto trimethoxysilane with a volume concentration of 0.3%, and stirred at room temperature for 30 - 50 min to obtain a coal gangue dispersion.
[0067] The organically modified sodium-based bentonite, styrene sulfonic acid, polyacrylamide and water are mixed evenly according to the mass-volume ratio of 1 g: 1 g: 1.5 g: 75 mL, and then strongly stirred. After that, ammonium persulfate (the addition amount is 0.45% of the mass of styrene sulfonic acid) is added for water bath heating and stirring reaction. After the reaction is completed, it is ultrasonically treated and left to age. The obtained product is dried to obtain modified polyacrylamide.
[0068] The obtained modified polyacrylamide (the addition amount is 2 times the mass of coal gangue) is added to the coal gangue dispersion and stirred for 14 h, then filtered. The obtained solid product is washed and dried to obtain a modified polyacrylamide-coupled coal gangue composite.
[0069] Polyethylene is dissolved in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 30%. Then, the air inside the fluidized bed equipment is heated to 75 °C by a heater, and then the modified polyacrylamide-coupled coal gangue composite is added to the fluidized bed through a feeding device to make the particles in a stable fluidized state; when the modified polyacrylamide-coupled coal gangue composite is heated to 50 °C, the polyethylene solution is pressurized, and the flow rate is controlled at 10 g / cm 2 , the polyethylene solution is sprayed onto the surface of the particles. Through the continuous driving of the fluidized bed, each surface of the particles will be evenly sprayed with the solute material, and finally a complete coating will be formed. After adding water to the obtained modified polyacrylamide-coupled coal gangue composite with a coating, it is successively subjected to ultrasonic treatment and drying to obtain the final product.
[0070] Comparative Example 4:
[0071] Mix organically modified sodium bentonite, styrene sulfonic acid, polyacrylamide and water in the amount of 1 g: 1 g: 1.5 g: 75 mL by mass-volume ratio, stir well, and then add ammonium persulfate (the addition amount is 0.45% of the mass of styrene sulfonic acid), and carry out a water bath heating and stirring reaction. After the reaction is completed, carry out ultrasonic treatment and static aging, and dry the obtained product to obtain modified polyacrylamide.
[0072] Dissolve polyethylene in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 30%. Then use a heater to heat the air inside the fluidized bed equipment to 75 °C, and then add the modified polyacrylamide into the fluidized bed through a feeding device to make the particles in a stable fluidized state. When the modified polyacrylamide is heated to 50 °C, pressurize the polyethylene solution and control the flow rate at 10 g / cm 2 , and spray the polyethylene solution onto the particle surface. Through the continuous driving of the fluidized bed, the solute material will be evenly sprayed on all sides of the particles, and finally a complete coating will be formed. After adding water to the obtained coated modified polyacrylamide, carry out ultrasonic treatment and drying in sequence to obtain the final product.
[0073] Comparative Example 5:
[0074] Soak the coal gangue in a hydrochloric acid solution with a concentration of 10 wt%, stir at 300 rpm at room temperature for 45 minutes, then take it out, wash it with deionized water, then calcine it at 500 °C for 7 hours, and finally grind it and pass through an 80-mesh sieve to obtain coal gangue powder.
[0075] Mix the obtained coal gangue powder and Fe-MOF in a mass ratio of 1:2, disperse them ultrasonically in a hydrolyzed solution of mercapto trimethoxysilane with a volume concentration of 0.3%, and stir at room temperature for 30 - 50 minutes to obtain a coal gangue / Fe-MOF dispersion.
[0076] Then filter, wash and dry the obtained solid product to obtain coal gangue / Fe-MOF.
[0077] Dissolve polyethylene in tetrachloroethylene to obtain a polyethylene solution with a mass fraction of 30%. Then use a heater to heat the air inside the fluidized bed equipment to 75 °C, and then add the coal gangue / Fe-MOF composite into the fluidized bed through a feeding device to make the particles in a stable fluidized state. When the coal gangue / Fe-MOF composite is heated to 50 °C, pressurize the polyethylene solution and control the flow rate at 10 g / cm 2 , and spray the polyethylene solution onto the particle surface. Through the continuous driving of the fluidized bed, the solute material will be evenly sprayed on all sides of the particles, and finally a complete coating will be formed. After adding water to the obtained coated coal gangue / Fe-MOF composite, carry out ultrasonic treatment and drying in sequence to obtain the final product.
[0078] Application Example 1: Sewage treatment effects of different products
[0079] Weigh 5 g of the products of Examples 1-3 and Comparative Examples 1-5 respectively, and place them in conical flasks. Add 100 mL of the sewage to be treated (sewage from a leather factory in Hebei Province, and the relevant pollution indicators are: BOD is 405 mg / L; COD is 1250 mg / L; SS is 115 mg / L; total chromium is 9.3 mg / L; chromaticity is 250 times) to each conical flask. Place the conical flasks in an oscillator and oscillate at 200 rpm for 40 min, then let it stand for 1 day. Take the supernatant to measure the content of each sewage index, and the results are shown in Table 1.
[0080] Table 1 Sewage indexes of each group
[0081] Group BOD (mg / L) COD (mg / L) SS (mg / L) Total Chromium (mg / L) Colority (times) Example 1 35 62 36 0.4 20 Example 2 46 73 47 0.8 35 Example 3 41 64 43 0.6 30 Comparative Example 1 52 91 50 1.1 45 Comparative Example 2 67 107 55 1.5 56 Comparative Example 3 93 165 59 2.1 61 Comparative Example 4 238 408 88 4.7 124 Comparative Example 5 206 369 79 3.9 113
[0082] As can be seen from the results in Table 1, compared with the control examples where the coal gangue in Comparative Example 1 was not modified, no coal gangue was added in Comparative Example 2, no Fe-MOF was added in Comparative Example 3, neither coal gangue nor Fe-MOF was added simultaneously in Comparative Example 4, and no modified polyacrylamide was added in Comparative Example 5, the product of Example 1 of the present invention can significantly improve the treatment effect on the pollutants in leather wastewater, and Examples 2 and 3 are both superior to Comparative Examples 1-5. The above results show that the membrane treatment agent of the present invention has excellent sewage treatment effect and can be used for the effective treatment of leather wastewater.
[0083] The above is only the preferred embodiment of the present invention, and it does not impose any form of limitation on the present invention. Although the present invention has been disclosed above with the preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications in the equivalent form within the scope of the technical solution of the present invention by using the above-disclosed methods and technical contents, but as long as it does not depart from the content of the technical solution of the present invention, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a membrane agent for wastewater treatment, characterized in that: The method comprises the following steps: S1: soaking the coal gangue in acid, taking it out, washing it with deionized water, and then calcining and grinding it to obtain coal gangue powder; S2: uniformly mixing the obtained coal gangue powder and the iron-based metal organic framework material in a mass ratio of 1:1-3, and then ultrasonically dispersing them in a silane coupling agent hydrolyzate having a volume concentration of 0.1-0.5%, and stirring them at room temperature for 30-50 minutes to obtain a coal gangue / iron-based metal organic framework material dispersion; S3: Mix the organic modified sodium bentonite, functional monomer, polyacrylamide and water in a mass volume ratio of 1g:1g:1~2 g:50~100mL and stir vigorously, then add the initiator to heat and stir in a water bath for reaction, ultrasonicate and stand for aging after the reaction, and dry the obtained product to obtain modified polyacrylamide; S4: adding the obtained modified polyacrylamide to the coal gangue / iron-based metal organic framework material dispersion and stirring for 12 to 16 hours, then filtering, washing and drying the obtained solid product to obtain a modified polyacrylamide coupled coal gangue / iron-based metal organic framework material composite; S5: The coating material is dissolved in an organic solvent to obtain a coating liquid with a mass fraction of 20-40%, and then the coating liquid is sprayed onto the surface of the modified polyacrylamide-coupled coal gangue / iron-based metal organic framework material composite by a fluidized bed for coating. The obtained coated modified polyacrylamide-coupled coal gangue / iron-based metal organic framework material composite is subjected to ultrasound and drying in sequence to obtain the final product.
2. The preparation method according to claim 1, characterized in that: In step S1, The acid soaking is as follows: soaking the coal gangue in acid at room temperature and stirring at 200-400 rpm for 30-60 minutes; The calcination is as follows: the cleaned coal gangue is calcined at 400-600° C. for 4-10 hours.
3. The preparation method according to claim 2, characterized in that: The acid is selected from at least one of hydrochloric acid, nitric acid and sulfuric acid.
4. The preparation method according to claim 1, characterized in that: In step S2, the silane coupling agent hydrolyzate is obtained by dissolving the silane coupling agent in ethanol, and the silane coupling agent is selected from any one of mercaptotrimethoxysilane, mercaptotriethoxysilane, mercaptomethyltrimethoxysilane, mercaptomethyltriethoxysilane, and mercaptomethyltripropoxysilane.
5. The preparation method according to claim 1, characterized in that: In step S3, the method for preparing the organically modified sodium bentonite comprises the following steps: (i) adding sodium bentonite to water in a mass volume ratio of 1 g: 10-30 mL, heating in a water bath at 50-70° C. with stirring for 1-3 h, then ultrasonicating for 20-40 min and standing for 3-5 h to obtain a sodium bentonite slurry; (ii) adding a surfactant to the obtained sodium bentonite slurry, heating the mixture in a water bath at 60-80° C. with stirring for 1-3 hours to obtain an organically modified sodium bentonite.
6. The preparation method according to claim 5, characterized in that: In step (ii), the surfactant is a quaternary ammonium salt surfactant, selected from any one of dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride; The added amount of the surfactant is 1-3% of the mass of the sodium bentonite.
7. The preparation method according to claim 1, characterized in that: In step S3, the functional monomer is selected from one or more of maleic anhydride, maleic acid, styrene sulfonic acid, vinyl benzoic acid, and vinyl phosphonic acid.
8. The preparation method according to claim 1, characterized in that: In step S3, the initiator is selected from any one of potassium persulfate, ammonium persulfate, and sodium persulfate; The amount of the initiator added is 0.3-0.6% of the mass of the functional monomer.
9. The preparation method according to claim 1, characterized in that: In step S4, the amount of modified polyacrylamide added is 1 to 3 times the mass of the gangue / iron-based metal organic framework material.
10. The preparation method according to claim 1, characterized in that: In step S5, the coating material is selected from one or more of polyolefin, polyurethane, natural rubber, urea-formaldehyde resin, and epoxy resin; The organic solvent is selected from one or more of tetrachloroethylene, dichloromethane, n-hexane, xylene and acetone.